A method for preparing super-large-sized graphene tubes by rapid self-assembly in batches without template

Through the rapid self-assembly method of batch without templates, high-temperature carbonization treatment of carbonaceous substances and alkaline earth metals, the complexity and low yield of the existing graphene tube preparation methods are solved, and graphene tube preparation with ultra-large size and ultra-thick tube walls is achieved, which is suitable for industrial production.

CN118929641BActive Publication Date: 2025-05-02GUANGDONG UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410987029.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-23
Publication Date
2025-05-02
Estimated Expiration
2044-07-23

AI Technical Summary

Technical Problem

The existing graphene tube preparation methods have problems such as expensive equipment, complex process, small product tube diameter, low purity and low yield, which limits the industrial production of graphene tubes.

Method used

The ultra-large-size graphene tube is prepared by mixing carbonaceous substances that can self-assemble into graphite phase carbon nitride polymers with alkaline earth metals and carbonized at high temperatures.

Benefits of technology

It has achieved the preparation of micron-scale graphene tubes with ultra-large size, ultra-thick tube walls and obvious bamboo joints. The process is simple, the product tube diameter is large, the purity is high, and the output is large, which is suitable for large-scale industrial preparation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118929641B_ABST
    Figure CN118929641B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for preparing ultra-large-sized graphene tubes by rapid self-assembly in batches without templates, which relates to the technical field of carbon materials and comprises the following steps: S1, using a carbon-containing substance that can self-assemble into a graphite-phase carbon nitride polymer as a carbon source, using an alkaline earth metal element and / or an alkaline earth metal compound as an auxiliary material, and uniformly mixing the carbon source and the auxiliary material to obtain a mixed raw material; S2, loading the mixed raw material into a graphite reaction chamber, and placing the graphite reaction chamber in an oxygen-free environment at a temperature above 900°C for carbonization treatment to obtain a micron-sized graphene tube. The present invention can prepare a micron-sized graphene tube without the need for a template and a CVD device, etc., has a simple process, a large product tube diameter, high purity, and a large output, and can be prepared on a large scale industrially.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of carbon materials, and in particular to a method for preparing super-large-sized graphene tubes by rapid batch self-assembly without templates. Background Art

[0002] Graphene is a two-dimensional hexagonal close-packed lattice structure formed by tightly stacked single-layer carbon atoms. It is the thinnest known nanomaterial with the best mechanical properties and is the basic unit for constructing other dimensional carbonaceous materials. A tubular material curled up from a single or multi-layer graphene is a graphene tube. Compared with carbon nanotubes, the ends of graphene tubes are not sealed and can undergo secondary growth to obtain ultra-long hollow tubular structures. Graphene tubes not only have the unique physical and chemical properties of graphene and the one-dimensional hollow structural characteristics of graphene, but can also effectively regulate the charge distribution of graphene. Compared with carbon nanotubes, their tube diameter is larger, and their performance in conductivity, field emission, oxygen reduction, electrochemistry, etc. is better, and they have broader application prospects.

[0003] However, due to the limitations of the preparation methods of graphene tubes, the research on graphene tubes is still in its early stages. The currently reported preparation of graphene tubes mainly uses template vapor deposition (CVD) technology, which has limitations such as expensive equipment, complex process, small product tube diameter, low purity, and low yield. As a result, the preparation of graphene tubes still remains in the laboratory and cannot be achieved in large-scale industrial production. Summary of the invention

[0004] The purpose of the present invention is to overcome the shortcomings of the prior art. The present invention provides a method for preparing ultra-large-sized graphene tubes by rapid batch self-assembly without a template. The method comprises mixing a carbon-containing substance that can self-assemble into a graphite-phase carbon nitride polymer with an alkaline earth metal (element and / or compound) and carbonizing them at a high temperature. No template and CVD device are required, and the micron-sized graphene tube can be prepared. The process is simple, the product has a large tube diameter, high purity, and large output, and can be prepared on a large scale on an industrial scale.

[0005] The present invention provides a method for preparing ultra-large-sized graphene tubes by rapid self-assembly in batches without a template, comprising the following steps:

[0006] S1, using a carbon-containing substance that can self-assemble into a graphite-phase carbon nitride polymer as a carbon source, and using an alkaline earth metal element and / or an alkaline earth metal compound as an auxiliary material, and uniformly mixing the carbon source and the auxiliary material to obtain a mixed raw material;

[0007] S2, loading the mixed raw material into a graphite reaction chamber, and placing the graphite reaction chamber in an oxygen-free environment above 900° C. for carbonization treatment to obtain micron-sized graphene tubes.

[0008] Specifically, the auxiliary material accounts for 0.5-20% of the mass of the mixed raw material.

[0009] Specifically, the proportion of graphene tubes with a diameter ranging from 1 to 2 μm in the micron-sized graphene tubes is ≥ 75%, and the length of the micron-sized graphene tubes is ≥ 50 μm.

[0010] Specifically, the carbon source includes one or more of cyanamide, dicyandiamide, melamine, urea, thiourea, cyanuric acid, and cyanuric chloride;

[0011] The auxiliary material includes one or more of calcium, magnesium, strontium, barium and their compounds.

[0012] Specifically, the calcium compound in the auxiliary material includes one or more of calcium carbonate, calcium bicarbonate, calcium oxide, calcium hydroxide, calcium hydride, calcium peroxide, calcium chloride, calcium fluoride, calcium carbide, calcium cyanamide, calcium hypochlorite, and calcium sulfate.

[0013] Specifically, the oxygen-free environment is a vacuum environment, or the oxygen-free environment is created by a protective atmosphere.

[0014] Specifically, step S1 includes:

[0015] S11, grinding the carbon source and the auxiliary material in a mortar to obtain a first mixed material;

[0016] S12, dispersing the first mixed material in deionized water to obtain a homogeneous suspension;

[0017] S13, heating and drying the homogeneous suspension in a water bath to obtain a second mixed material;

[0018] S14, grinding the second mixed material in a mortar to obtain the mixed raw material.

[0019] Specifically, in step S12, the mass of the deionized water is 5 to 10 times that of the first mixture;

[0020] In step S13, the temperature range of the water bath condition is 50-70°C.

[0021] Specifically, step S2 includes:

[0022] S21, loading the mixed raw material into a graphite reaction chamber, and placing at least two layers of carbon cloth at a preset distance above the mixed raw material;

[0023] S22, placing the graphite reaction chamber in a crucible, and then placing the crucible in a vacuum tube furnace;

[0024] S23, in an oxygen-free environment, heating the mixed raw material to a preset temperature at a preset heating rate, and keeping the temperature at the preset temperature for a preset time;

[0025] S24. After the vacuum tube furnace is cooled, black flocculent products are collected on the at least two layers of carbon cloth, and the black flocculent products are the micron-sized graphene tubes.

[0026] Specifically, in step S21, the preset distance is 1 to 10 cm;

[0027] In step S23, the preset heating rate is 5-20°C / min, the preset temperature is 900-3000°C, and the preset time is at least 30 minutes.

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] In the present invention, a carbon-containing substance that can self-assemble into a graphite-phase carbon nitride polymer is used as a carbon source. Such carbon source will decompose and polycondense in an oxygen-free environment above 900°C to form a graphite-phase carbon nitride cluster flaky product; an alkaline earth metal element and / or an alkaline earth metal compound is used as an auxiliary material. Such auxiliary material has a catalytic effect, can support the graphite-phase carbon nitride cluster flaky product to self-assemble into a tubular structure in situ in an oxygen-free environment above 900°C, and promote the radial and axial growth of the tubular structure to form a micron-sized graphene tube with an ultra-large size, an ultra-thick tube wall and a distinct bamboo-node morphology. No template and CVD device are required throughout the process, and no carbon source, nitrogen source and transition metal catalyst need to be supplemented. The process is simple, the product has a large tube diameter, high purity and a large output, and can be prepared on a large scale on an industrial scale. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0031] Figure 1 It is a schematic flow chart of a method for preparing ultra-large-sized graphene tubes by rapid self-assembly in batches without templates according to an embodiment of the present invention;

[0032] Figure 2 is a schematic flow chart of step S1 in an embodiment of the present invention;

[0033] Figure 3 is a schematic flow chart of step S2 in an embodiment of the present invention;

[0034] Figure 4 is a SEM image of the micrometer-sized graphene tube of Example 1 with a scale of 50.0 μm;

[0035] Figure 5is a SEM image of the micrometer-sized graphene tube of Example 1 with a scale of 20.0 μm;

[0036] Figure 6 is a SEM image of the micrometer-sized graphene tube of Example 1 with a scale of 10.0 μm;

[0037] Figure 7 is a SEM image of the micrometer-sized graphene tube of Example 1 with a scale of 2.0 μm;

[0038] Figure 8 is an X-ray element mapping diagram of the micron-scale graphene tube of Example 1;

[0039] Fig. 9 is the energy spectrum of the micron-sized graphene tube of Example 1;

[0040] Fig.10 is the XPS overall spectrum of the micron-sized graphene tube of Example 1;

[0041] Fig.11 is a high-resolution C1s spectrum of the micron-sized graphene tube of Example 1;

[0042] Fig.12 is the XRD spectrum of the micron-sized graphene tube of Example 1;

[0043] Fig.13 is the Raman spectrum of the micron-sized graphene tube of Example 1;

[0044] Fig.14 is the FTIR infrared spectrum of the micron-sized graphene tube of Example 1;

[0045] Fig.15 is a TEM photograph of the micrometer-sized graphene tube of Example 1 with a scale of 2.0 μm;

[0046] Fig.16 is a TEM photograph of the micrometer-sized graphene tube of Example 1 with a scale of 1.0 μm;

[0047] Fig.17 is a TEM photograph of the micrometer-sized graphene tube of Example 1 with a scale of 500.0 nm;

[0048] Fig.18 is a TEM photograph of the micrometer-sized graphene tube of Example 1 with a scale of 100.0 nm;

[0049] Fig.19 yes Fig.18 TEM image of micrometer-sized graphene tubes in area A, with a scale of 20.0 nm;

[0050] Fig. 20 yes Fig.18TEM image of micrometer-sized graphene tubes in region B, with a scale of 10.0 nm;

[0051] Fig.21 is a SEM image of the micrometer-sized graphene tube of Example 4 with a scale of 10.0 μm;

[0052] Fig. 22 is a SEM image of the micrometer-sized graphene tube of Example 5 with a scale of 10.0 μm;

[0053] Fig.23 is a SEM image of the micrometer-sized graphene tube of Example 6 with a scale of 5.0 μm;

[0054] Fig.24 is a SEM image of the micrometer-sized graphene tube of Example 7 with a scale of 5.0 μm;

[0055] Fig.25 is a SEM image of the graphene tube of Comparative Example 1 with a scale of 50.0 μm;

[0056] Fig.26 is a SEM image of the graphene tube of Comparative Example 1 with a scale of 10.0 μm;

[0057] Fig. 27 is a SEM image of the graphene tube of Comparative Example 1 with a scale of 5.0 μm;

[0058] Fig.28 This is a SEM image of the graphene tube of Comparative Example 1 with a scale of 2.0 μm. DETAILED DESCRIPTION

[0059] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0060] Figure 1 A schematic flow chart of a method for preparing ultra-large-sized graphene tubes by rapid self-assembly in batches without templates according to an embodiment of the present invention is shown, comprising the following steps:

[0061] S1, using a carbon-containing substance that can self-assemble into a graphite-phase carbon nitride polymer as a carbon source, and using an alkaline earth metal element and / or an alkaline earth metal compound as an auxiliary material, and uniformly mixing the carbon source and the auxiliary material to obtain a mixed raw material;

[0062] Carbon-containing substances that can self-assemble into graphite-phase carbon nitride polymers (g-C3N4) will decompose and condense in a high-temperature, oxygen-free environment to form graphite-phase carbon nitride cluster flake products; alkaline earth metal elements have active chemical properties and are easily converted into catalytically active alkaline earth metal oxides during the mixing process; alkaline earth metal compounds themselves have catalytic effects, or alkaline earth metal compounds will decompose in a high-temperature environment to produce catalytic products; thereby supporting the in-situ self-assembly of graphite-phase carbon nitride cluster flake products into tubular structures in a high-temperature, oxygen-free environment, and promoting the radial and axial growth of the tubular structure.

[0063] The carbon source and the auxiliary materials are mixed evenly so that the carbon source and the auxiliary materials are fully in contact, which is conducive to the subsequent reaction. There are many ways to mix, such as stirring and mixing, grinding and mixing, and dispersing in an aqueous environment, etc., which are selected according to the properties of the raw materials. Among them, when mixing the carbon source and the auxiliary materials, the particle size of the carbon source is above the micron level, and the particle size of the auxiliary materials is at the nanometer level, which is conducive to the subsequent acquisition of super-large-sized graphene tubes.

[0064] Specifically, the auxiliary material accounts for 0.5-20% of the mass of the mixed raw material. If the auxiliary material is too little, the catalytic effect is poor and the reaction efficiency is low; if the auxiliary material is too much, the morphology and size of the graphene tube will be affected.

[0065] In some specific embodiments, the carbon source includes one or more of cyanamide, dicyandiamide, melamine, urea, thiourea, cyanuric acid, and cyanuric chloride, all of which can decompose and condense in a high temperature and oxygen-free environment to form graphite-phase carbon nitride cluster flaky products; preferably, the carbon source is melamine or dicyandiamide, which has a high carbon content and is easy to self-assemble into graphite-phase carbon nitride polymers.

[0066] In some specific embodiments, the auxiliary materials include one or more of calcium, magnesium, strontium, barium and their compounds. The chemical properties of calcium, magnesium, strontium and barium are active, and they are easily converted into catalytically active calcium oxide, magnesium oxide, strontium oxide and barium oxide during the mixing process; compounds of calcium, magnesium, strontium and barium, such as alkaline earth metal oxides and alkaline earth metal halides, have catalytic effects themselves, and alkaline earth metal carbonates, bicarbonates, sulfates, alkalis, etc. can decompose to produce alkaline earth metal oxides under high temperature environment, and can also play a catalytic role; alkaline earth metal hydrides, carbides, peroxides, hypochlorites, cyanamides, etc. can be converted into alkalis or salts in an aqueous environment, and then decomposed to produce alkaline earth metal oxides in a high temperature environment, which can also play a catalytic role. Some alkaline earth metal compounds will also produce carbon dioxide or oxygen when decomposed. These gases are trace and can be used as an etchant for amorphous carbon, which is beneficial to the subsequent growth of graphene tubes.

[0067] The auxiliary material mainly serves as a proppant for the graphite phase carbon nitride cluster flake products to curl into an initial tubular structure (bamboo morphology), and continuously provides support for the growth of each graphene tube.

[0068] Specifically, the calcium compound in the auxiliary material includes one or more of calcium carbonate, calcium bicarbonate, calcium oxide, calcium hydroxide, calcium hydride, calcium peroxide, calcium chloride, calcium fluoride, calcium carbide, calcium cyanamide, calcium hypochlorite, and calcium sulfate, which have a good catalytic effect on the growth of graphene tubes.

[0069] Preferably, the auxiliary material is calcium oxide or calcium carbonate or calcium bicarbonate or calcium hydroxide. Calcium oxide has a face-centered cubic structure, which can provide a growth plane for the rearrangement and oriented growth of graphite atoms, and is more conducive to the radial and axial growth of graphene tubes, forming a good bamboo morphology; while calcium carbonate, calcium bicarbonate and calcium hydroxide can decompose in a high temperature environment to form calcium oxide, which can also produce the same effect.

[0070] In some specific embodiments, Figure 2 The flowchart of step S1 in the embodiment of the present invention is shown, and step S1 includes:

[0071] S11, grinding the carbon source and the auxiliary material in a mortar to obtain a first mixed material;

[0072] Specifically, the mortar is a quartz mortar with high hardness and wear resistance. Usually, the grinding is performed for at least 30 minutes to ensure that the carbon source and the auxiliary materials are evenly mixed.

[0073] S12, dispersing the first mixed material in deionized water to obtain a homogeneous suspension;

[0074] The first mixture can be dispersed in deionized water by stirring, ultrasonic treatment and the like, which is conducive to further improving the mixing uniformity of the carbon source and the auxiliary materials; wherein the deionized water is 5 to 10 times the mass of the first mixture, ensuring that the first mixture can be fully dispersed while avoiding excessive deionized water to facilitate subsequent drying.

[0075] S13, heating and drying the homogeneous suspension in a water bath to obtain a second mixed material;

[0076] Water bath heating is gentler and more uniform, and can avoid material agglomeration; specifically, the temperature range of the water bath condition is 50-70° C., which is conducive to maintaining the mixing uniformity of the carbon source and the auxiliary materials.

[0077] S14, grinding the second mixed material in a mortar to obtain the mixed raw material;

[0078] Specifically, the mortar is a quartz mortar with high hardness and wear resistance. Usually, the grinding is performed for at least 30 minutes, so that the carbon source and the auxiliary materials are mixed evenly and loosely, which is conducive to the subsequent reaction and has a positive effect on the size of the graphene tube.

[0079] S2, loading the mixed raw material into a graphite reaction chamber, and placing the graphite reaction chamber in an oxygen-free environment above 900° C. for carbonization treatment to obtain micron-sized graphene tubes.

[0080] The graphite reaction chamber has excellent high temperature resistance and can withstand chemical reactions in high temperature environments. Moreover, graphite materials show good stability in a variety of chemical environments and are not prone to unnecessary chemical reactions with reactants, thus ensuring the purity and quality of the graphene tube preparation process.

[0081] The carbon source in the mixed raw materials will decompose and condense in an oxygen-free environment above 900°C to form graphite-phase carbon nitride cluster flaky products; the auxiliary materials in the mixed raw materials have a catalytic effect, which can support the in-situ self-assembly of the graphite-phase carbon nitride cluster flaky products into a tubular structure in an oxygen-free environment above 900°C, and promote the radial and axial growth of the tubular structure to form ultra-large size, ultra-thick tube wall, bamboo-node morphology of micron-scale graphene tubes, the whole process does not require templates and CVD devices, and does not require the addition of carbon sources, nitrogen sources and transition metal catalysts, the process is simple, the product has a large tube diameter, high purity, and large output, and can be prepared on a large scale industrially.

[0082] Specifically, the diameter of the micron-scale graphene tube is greater than 500nm, and the length of the micron-scale graphene tube is ≥50μm; among them, the proportion of graphene tubes with a diameter range of 1 to 2μm is ≥75%. Compared with existing nano-scale graphene tubes, micron-scale graphene tubes are super large in size, have better performance in conductivity, field emission, oxygen reduction, electrochemistry, etc., and have broader application prospects.

[0083] Furthermore, the oxygen-free environment is a vacuum environment, or the oxygen-free environment is created by a protective atmosphere; the oxygen-free environment can prevent the carbon source from burning.

[0084] In some specific implementations, Figure 3 The flowchart of step S2 in the embodiment of the present invention is shown, and step S2 includes:

[0085] S21, loading the mixed raw material into a graphite reaction chamber, and placing at least two layers of carbon cloth at a preset distance above the mixed raw material;

[0086] Carbon cloth, also known as carbon fiber cloth, has the characteristics of high temperature resistance, high strength, low density, excellent tensile and fracture resistance, etc. The carbon cloth is spaced above the mixed raw materials, and the micron-sized graphene tubes produced by the subsequent reaction can be attached to the surface of the carbon cloth to prevent the micron-sized graphene tubes from mixing with the raw materials, thereby obtaining high-purity micron-sized graphene tube products and preventing product overflow.

[0087] Specifically, the preset distance is 1 to 10 cm. If the preset distance is less than 1 cm, the graphene tube product is easily sintered, affecting the morphology and quality of the product; if the preset distance is greater than 10 cm, the product is difficult to adhere to the carbon cloth, making it inconvenient to collect high-purity micron-level graphene tube products.

[0088] S22, placing the graphite reaction chamber in a crucible, and then placing the crucible in a vacuum tube furnace;

[0089] Using a crucible to load the graphite reaction chamber is convenient for transfer and has a good protective effect on the graphite reaction chamber.

[0090] S23, in an oxygen-free environment, heating the mixed raw material to a preset temperature at a preset heating rate, and keeping the temperature at the preset temperature for a preset time;

[0091] Specifically, the preset heating rate is 5-20°C / min, the preset temperature is 900-3000°C, and the preset duration is at least 30 minutes, which can ensure the complete decomposition of the carbon source and avoid catalyst agglomeration, so that the graphene tube grows smoothly. Preferably, in an oxygen-free environment, the mixed raw material is heated to 900-1500°C at a heating rate of 10°C / min and kept warm for 30 minutes, and the obtained micron-scale graphene tube has a good morphology.

[0092] S24. After the vacuum tube furnace is cooled, black flocculent products are collected on the at least two layers of carbon cloth, and the black flocculent products are the micron-sized graphene tubes.

[0093] The micron-sized graphene tubes are light in weight and will float and adhere to the carbon cloth. The micron-sized graphene tubes collected from the carbon cloth are of extremely high purity.

[0094] In the present invention, a carbon-containing substance that can self-assemble into a graphite-phase carbon nitride polymer is used as a carbon source. Such carbon source will decompose and polycondense in an oxygen-free environment above 900°C to form a graphite-phase carbon nitride cluster flaky product; an alkaline earth metal element and / or an alkaline earth metal compound is used as an auxiliary material. Such auxiliary material has a catalytic effect, can support the graphite-phase carbon nitride cluster flaky product to self-assemble into a tubular structure in situ in an oxygen-free environment above 900°C, and promote the radial and axial growth of the tubular structure to form a micron-sized graphene tube with an ultra-large size, an ultra-thick tube wall and a distinct bamboo-node morphology. No template and CVD device are required throughout the process, and no carbon source, nitrogen source and transition metal catalyst need to be supplemented. The process is simple, the product has a large tube diameter, high purity and a large output, and can be prepared on a large scale on an industrial scale.

[0095] The traditional process of preparing nitrogen-doped graphene tubes using expensive iron-based, cobalt-based, nickel-based and other materials as catalysts is a carbon deposition process that grows from the bottom or the top, and the growth of the graphene tubes will be affected by the catalyst particle size; however, the self-assembly process of the graphene tubes of the present invention is not affected by the auxiliary material particle size, and the graphite phase carbon nitride cluster sheet products are self-assembled and curled into tubular products in a high-temperature oxygen-free environment. The auxiliary materials play a supporting and guiding role in the initial growth process of the tubular products, which can prevent the tubular products from collapsing, so that the tubular products can continuously self-assemble at the bottom for axial growth.

[0096] Compared with conventional nitrogen-doped graphene tubes prepared using expensive iron-based, cobalt-based, nickel-based and other materials as catalysts, the graphene tubes prepared by the present invention are not only ultra-large in size and high in purity, but also free of nitrogen and have a high degree of graphitization.

[0097] Example 1

[0098] (1) Weigh 1.8 g of melamine (purity: 99%) and 0.2 g of calcium carbonate (particle size: 50 nm), place them in a quartz mortar and grind them for 30 min to obtain a mixed raw material;

[0099] (2) The mixed raw material is placed in a graphite reaction chamber, and two layers of carbon cloth are placed 5 cm above the mixed raw material;

[0100] (3) placing the graphite reaction chamber in a crucible, and then placing the crucible in a vacuum tube furnace;

[0101] (4) In a protective atmosphere, start the heating program of the vacuum tube furnace, starting from room temperature and heating to 1200°C at a heating rate of 10°C / min;

[0102] (5) The mixture was kept at 1200° C. for 30 min, and then the vacuum tube furnace was naturally cooled to room temperature. Black flocculent products were collected on the carbon cloth. The black flocculent products were micron-sized graphene tubes.

[0103] Example 1 Using melamine as a carbon source and calcium carbonate as an auxiliary material, high-temperature carbonization treatment is carried out to prepare ultra-large-sized graphene tubes by rapid self-assembly in batches without a template. The raw material system is simple, easy to obtain, and economical. The prepared micron-sized graphene tubes are of high purity and easy to collect, which is convenient for industrial production.

[0104] Melamine is easy to decompose and polycondense under high temperature to form graphite phase carbon nitride cluster flake products. With the increase of local concentration of graphite phase carbon nitride and gaseous diffusion, graphite phase carbon nitride cluster flake products will self-assemble to form a tubular structure. At the same time, calcium carbonate will decompose to form calcium oxide and carbon dioxide under high temperature. Carbon dioxide can be used as an etchant for amorphous carbon to prevent the accumulation of amorphous carbon. The overflow of carbon dioxide is conducive to the formation of the open morphology at the end of the graphene tube, thereby improving the generation efficiency of the graphene tube. Calcium oxide has a high melting point and is in the form of solid particles in a high temperature environment. , which can serve as a proppant for the graphene tube to curl into the initial bamboo-joint morphology, and continue to provide support for the growth of each graphene tube, thereby improving the orientation of the graphene tube growth and significantly increasing the straightness of the tube structure; subsequently, the graphene tube can grow axially using itself as a template. As the graphene tube grows, under the action of external tension, some calcium oxide particles naturally fall off and serve as a proppant to catalyze the formation of a new tube structure, which can be recycled; ultimately, the generated tube structure exhibits a micron-scale, ultra-large size, multi-layer, thick-walled, and axially multiple-growth bamboo-joint morphology.

[0105] Figure 4 The SEM image of the micrometer-scale graphene tube of Example 1 with a scale of 50.0 μm is shown. Figure 5 The SEM image of the micrometer-sized graphene tube of Example 1 with a scale of 20.0 μm is shown. Figure 6 The SEM image of the micrometer-scale graphene tube of Example 1 with a scale of 10.0 μm is shown. Figure 7 The SEM image of the micron-sized graphene tube of Example 1 with a scale of 2.0 μm is shown. By observing the SEM images of the micron-sized graphene tube of Example 1 at different magnifications, it is found that the micron-sized graphene tube of Example 1 has high purity, is almost entirely a tubular structure product, has no auxiliary material residue, and does not require post-treatment such as product pickling; the sizes of these tubular structure products are generally uniform, with high straightness, and the radial dimensions are generally distributed in the micron level, the tube diameter is basically 1 to 2 μm, and the axial dimensions are all above 50 μm. Some micron-sized graphene tubes continue to grow for more than 200 μm; the appearance and morphology of the micron-sized graphene tube presents an obvious bamboo-section morphology, the axial dimension of a single-section graphene tube is 2 to 3 um, which is about 1.5 times the tube diameter, and the end of the micron-sized graphene tube is open.

[0106] Figure 8The X-ray element mapping diagram of the micron-scale graphene tube of Example 1 is shown, and it can be seen that the C element is evenly distributed along the graphene tube product, the O element content is low, the Ca element content is extremely low, and the Ca element is mainly accumulated at the root of the tube instead of being evenly distributed along the tube. The element distribution spectrum of the N element is not obtained. Fig. 9 The energy spectrum of the micron-scale graphene tube of Example 1 is shown, and Figure 8 Element mapping Figure 1 The graphene tube product is mainly composed of C element, of which the mass fraction of C element is as high as 85.489%, the mass fraction of Ca element is extremely trace, and the content of O element is also very low. The O element mainly comes from the adsorbed oxygen in the air and trace CaO products, and there is no N element content in the region. It can be inferred that the main component of the graphene tube prepared by co-heating melamine and calcium carbonate is C element, and there is very little CaO residue. The graphene tube product is clean and high in purity.

[0107] Fig.10 The XPS total spectrum of the micron-scale graphene tube of Example 1 shows two peaks. The stronger signal peak at about 284 eV corresponds to the peak of C1s; the very weak signal peak at about 532 eV corresponds to the peak of O1s, which mainly comes from the adsorbed O in the air; the signal peaks of N and Ca elements are not detected in the XPS total spectrum, indicating that the relative atomic concentrations of N and Ca elements in the graphene tube product are extremely low, which is consistent with the Fig. 9 The energy spectrum data are basically consistent. It can be determined that the main component of the graphene tube product prepared by co-heating melamine and calcium carbonate is C element, and the elements such as Ca and N are extremely low. The product is directly a high-purity graphene tube.

[0108] Fig.11 The high-resolution C1s spectrum of the micron-sized graphene tube of Example 1 is shown, and the C1s high-resolution spectrum is further peak-fitted. Considering that the main component of the graphene tube product is C element, and there is a wide and asymmetric tailing peak in the obtained C1s spectrum, extending in the direction of higher binding energy, it means that the graphene tube product is mainly a material connected by sp2 hybridization. Therefore, the corresponding 284.0eV (CC bond) is used as calibration, and the C1s peak is fitted into three peaks: the main peak at 284eV corresponds to the large conjugated bond C=C formed by sp2 hybridized carbon atoms in graphene, and the peak near 286.07eV is attributed to the adsorbed oxygen, corresponding to the CO bond; the peak at 290.07eV corresponds to the π-π* interaction between different carbon components and different graphene layers in the graphene tube, indicating that after being treated at a temperature of 1200°C, the product has graphitization characteristics.

[0109] Fig.12The XRD spectrum of the micron-sized graphene tube of Example 1 is shown. Through further XRD diffraction characterization, the carbon product has only one (002) peak at 2θ=26.34°, which indicates that the obtained carbon product has a high purity and a narrow diffraction peak, which means that the carbon product has a high degree of graphitization and few lattice defects. The graphite peak appears at around 26.5° relative to the single-walled carbon nanotube, which is due to the peak position shifting to the left due to the number of graphene tube layers, and due to the uneven curvature and tube diameter of the graphene tube, the (002) diffraction peak presents an asymmetric peak shape.

[0110] Fig.13 The Raman spectrum of the micron-scale graphene tube of Example 1 is shown. The Raman spectrum of the product has three characteristic peaks, which are located at 1350 cm -1 、1580cm -1 and 2700cm -1 , corresponding to the D peak, G peak and G′ peak of graphene respectively. Among them, 1350cm -1 The D peak at 1580cm is caused by amorphous carbon and material crystal defects, while the -1 The G peak that appears represents the in-plane stretching vibration of sp2 hybridized carbon. The intensity ratio of the D peak and the G peak can qualitatively analyze the degree of material defects (ID / IG). The larger the ratio, the lower the order of the carbon atoms inside the material. The ID / IG ratio of the tubular carbon product obtained by co-heating melamine and calcium carbonate is about 0.21, indicating that the tubular product has a high degree of graphitization at 1200°C. Combined with TEM analysis, it can be seen that the structural defects mainly come from the ultra-thick wall of the graphene tube, and at 2700cm -1 The G' peak is the secondary Raman scattering of the region boundary phonon, which is a double resonance process of the phonon wave vector and the electron energy band. The intensity ratio of the G' band to the G band (IG' / IG) has been used as an effective method to characterize the thickness of graphene or carbon tubes. Therefore, the smaller IG' / IG = 0.39 indicates that the thickness of the formed graphene tube is relatively large, indicating that the prepared graphene tube is composed of multilayer graphene.

[0111] Fig.14 This is the FTIR infrared spectrum of the micron-scale graphene tube of Example 1. The infrared spectrum of the carbon product does not contain about 812 cm -1 The absorption peak at 20° is at 10°, and its band corresponds to the characteristic breathing mode of s-triazine unit, indicating that the prepared carbon product is different from g-C3N4 nanotubes, which is consistent with the XPS total spectrum (see Fig.10 ) does not match the results of N content, 3600~3000cm -1The absorption peaks between 1090 and 1650 cm are mainly caused by the stretching vibration of NH or OH, which corresponds to the H2O molecules and amino groups bonded to the surface, indicating that the grown graphene tubes have more open surfaces. -1 The absorption peaks appearing in the region are mainly derived from the typical stretching vibration modes corresponding to C=0 and C-0, which further illustrates the vibration of the carbon skeleton in the carbon product, which is consistent with the Raman spectral activity.

[0112] Fig.15 The TEM image of the micrometer-scale graphene tube of Example 1 with a scale of 2.0 μm is shown. Fig.16 The TEM image of the micrometer-scale graphene tube of Example 1 with a scale of 1.0 μm is shown. Fig.17 The TEM photograph of the micron-scale graphene tube of Example 1 with a scale of 500.0 nm is shown. Fig.18 A TEM photograph of the micron-scale graphene tube of Example 1 with a scale of 100.0 nm is shown. It can be seen that the graphene tube presents an obvious periodic bamboo-node shape, and the tube wall thickness also presents a periodic change, increasing from the top of the bamboo node to the root, and a spacing layer is formed between the bamboo nodes.

[0113] Fig.19 Shows Fig.18 The TEM image of the micron-scale graphene tube in area A in the middle has a scale of 20.0 nm, corresponding to the spacer layer inside the tube; Fig. 20 Shows Fig.18 The TEM image of the micron-scale graphene tube in the B region is 10.0nm in scale, which corresponds to the position of the tube wall; the thickness of the tube wall changes along the cone, thus forming a unique bamboo-joint morphology. Both the tube wall and the spacer layer inside the tube show high crystallinity, with a crystal plane spacing of 0.34nm, which is consistent with the interlayer spacing of the (002) plane of graphite. Compared with the XRD spectrum (see Fig.12 ) representation remains consistent.

[0114] Example 2

[0115] (1) Weighing 1.8 g of melamine (purity: 99%) and 0.2 g of calcium carbonate (particle size: 50 nm), grinding them in a quartz mortar for 30 min to obtain a first mixture;

[0116] (2) placing the first mixed material in 10 g of deionized water, stirring with a magnetic stirrer at a speed of 350 r / min for 30 min, and then ultrasonically dispersing for 30 min to obtain a homogeneous suspension;

[0117] (3) heating the homogeneous suspension in a water bath at 60° C. until it is dried into powder to obtain a second mixed material;

[0118] (4) grinding the second mixed material in a quartz mortar for 30 minutes to obtain a mixed raw material;

[0119] (5) The mixed raw material is placed in a graphite reaction chamber, and two layers of carbon cloth are placed 5 cm above the mixed raw material;

[0120] (6) placing the graphite reaction chamber in a crucible, and then placing the crucible in a vacuum tube furnace;

[0121] (7) Start the vacuum pump to evacuate the vacuum, and then fill it with a protective atmosphere; in the protective atmosphere, start the heating program of the vacuum tube furnace, starting from room temperature and heating to 1200° C. at a heating rate of 10° C. / min;

[0122] (8) The mixture was kept at 1200°C for 30 min, and then the vacuum tube furnace was naturally cooled to room temperature. Black flocculent products were collected on the carbon cloth. The black flocculent products were micrometer-sized graphene tubes.

[0123] Different from Example 1, Example 2 adds a homogeneous suspension, drying and re-grinding treatment, so that the micron-scale graphene tubes finally obtained are more uniform in size and higher in straightness.

[0124] Example 3

[0125] (1) Weigh 0.95 g of melamine (purity: 99%) and 0.05 g of calcium oxide (particle size: 50 nm), place them in a quartz mortar and grind them for 30 min to obtain a mixed raw material;

[0126] (2) The mixed raw material is placed in a graphite reaction chamber, and two layers of carbon cloth are placed 5 cm above the mixed raw material;

[0127] (3) placing the graphite reaction chamber in a crucible, and then placing the crucible in a vacuum tube furnace;

[0128] (4) In a protective atmosphere, start the heating program of the vacuum tube furnace, starting from room temperature and heating to 900°C at a heating rate of 10°C / min;

[0129] (5) The mixture was kept at 900° C. for 30 min, and then the vacuum tube furnace was naturally cooled to room temperature. Black flocculent products were collected on the carbon cloth. The black flocculent products were micron-sized graphene tubes.

[0130] In Example 3, calcium oxide is directly used as an auxiliary material, and the obtained micron-scale graphene tube has an obvious bamboo-node morphology, and the tube diameter is basically 1 to 2 μm, but the ends of the graphene tube are mostly closed.

[0131] Example 4

[0132] (1) Weigh 0.95 g of melamine (purity: 99%) and 0.05 g of calcium bicarbonate (particle size: 50 nm), place them in a quartz mortar and grind them for 30 min to obtain a mixed raw material;

[0133] (2) The mixed raw materials were placed in a graphite reaction chamber, and two layers of carbon cloth were placed 10 cm above the mixed raw materials;

[0134] (3) placing the graphite reaction chamber in a crucible, and then placing the crucible in a vacuum tube furnace;

[0135] (4) In a protective atmosphere, start the heating program of the vacuum tube furnace, starting from room temperature and heating to 1500°C at a heating rate of 5°C / min;

[0136] (5) The mixture was kept at 1500° C. for 30 min, and then the vacuum tube furnace was naturally cooled to room temperature. Black flocculent products were collected on the carbon cloth. The black flocculent products were micron-sized graphene tubes.

[0137] Fig.21 An SEM image of the micron-sized graphene tube of Example 4 with a scale of 10.0 μm is shown. In the micron-sized graphene tube obtained in Example 4, the bamboo-node morphology is obvious, but the proportion of graphene tubes with a tube diameter range of 1 to 2 μm is slightly smaller.

[0138] Example 5

[0139] (1) Weigh 0.95 g of melamine (purity: 99%) and 0.05 g of magnesium carbonate (particle size: 50 nm), place them in a quartz mortar and grind them for 30 min to obtain a mixed raw material;

[0140] (2) The mixed raw material is placed in a graphite reaction chamber, and two layers of carbon cloth are placed 1 cm above the mixed raw material;

[0141] (3) placing the graphite reaction chamber in a crucible, and then placing the crucible in a vacuum tube furnace;

[0142] (4) In a protective atmosphere, start the heating program of the vacuum tube furnace, starting from room temperature and heating to 1200°C at a heating rate of 15°C / min;

[0143] (5) The mixture was kept at 1200° C. for 30 min, and then the vacuum tube furnace was naturally cooled to room temperature. Black flocculent products were collected on the carbon cloth. The black flocculent products were micron-sized graphene tubes.

[0144] Fig. 22 The SEM image of the micron-sized graphene tube of Example 5 with a scale of 10.0 μm is shown. In the micron-sized graphene tube obtained in Example 5, the bamboo-node morphology is obvious, but the proportion of graphene tubes with a tube diameter range of 1 to 2 μm is small.

[0145] Example 6

[0146] (1) Weigh 0.95 g of dicyandiamide (purity: 99%) and 0.05 g of magnesium carbonate (particle size: 50 nm), place them in a quartz mortar and grind them for 30 min to obtain a mixed raw material;

[0147] (2) The mixed raw material is placed in a graphite reaction chamber, and two layers of carbon cloth are placed 3 cm above the mixed raw material;

[0148] (3) placing the graphite reaction chamber in a crucible, and then placing the crucible in a vacuum tube furnace;

[0149] (4) In a protective atmosphere, start the heating program of the vacuum tube furnace, starting from room temperature and heating to 1000°C at a heating rate of 10°C / min;

[0150] (5) The mixture was kept at 1000° C. for 30 min, and then the vacuum tube furnace was naturally cooled to room temperature. Black flocculent products were collected on the carbon cloth. The black flocculent products were micron-sized graphene tubes.

[0151] Fig.23 The SEM image of the micron-scale graphene tube of Example 6 with a scale of 5.0 μm is shown. In the micron-scale graphene tube obtained in Example 6, the bamboo-node morphology is obvious, but the tube diameter is relatively thin and there is adhesion.

[0152] Example 7

[0153] (1) Weigh 0.95 g of dicyandiamide (purity: 99%) and 0.05 g of calcium oxide (particle size: 50 nm), place them in a quartz mortar and grind them for 30 min to obtain a mixed raw material;

[0154] (2) The mixed raw material is placed in a graphite reaction chamber, and two layers of carbon cloth are placed 8 cm above the mixed raw material;

[0155] (3) placing the graphite reaction chamber in a crucible, and then placing the crucible in a vacuum tube furnace;

[0156] (4) In a protective atmosphere, start the heating program of the vacuum tube furnace, starting from room temperature and heating to 2000°C at a heating rate of 20°C / min;

[0157] (5) The mixture was kept at 2000° C. for 30 min, and then the vacuum tube furnace was naturally cooled to room temperature. Black flocculent products were collected on the carbon cloth. The black flocculent products were micron-sized graphene tubes.

[0158] Fig.24An SEM image of the micron-sized graphene tube of Example 7 with a scale of 5.0 μm is shown. In the micron-sized graphene tube obtained in Example 7, the bamboo-node morphology is obvious, and the graphene tubes with a tube diameter range of 1 to 2 μm account for a large proportion. However, there are many particles on the surface of the graphene tubes, and the ends are mostly closed.

[0159] Example 8

[0160] (1) Weigh 0.95 g of dicyandiamide (purity: 99%) and 0.05 g of calcium hydroxide (particle size: 50 nm), place them in a quartz mortar and grind them for 30 min to obtain a mixed raw material;

[0161] (2) The mixed raw materials were placed in a graphite reaction chamber, and two layers of carbon cloth were placed 10 cm above the mixed raw materials;

[0162] (3) placing the graphite reaction chamber in a crucible, and then placing the crucible in a vacuum tube furnace;

[0163] (4) In a protective atmosphere, start the heating program of the vacuum tube furnace, starting from room temperature and heating to 1100°C at a heating rate of 10°C / min;

[0164] (5) The mixture was kept at 1100° C. for 30 min, and then the vacuum tube furnace was naturally cooled to room temperature. Black flocculent products were collected on the carbon cloth. The black flocculent products were micron-sized graphene tubes.

[0165] In the micron-scale graphene tubes obtained in Example 8, the bamboo-node morphology is obvious, and the graphene tubes with a tube diameter range of 1 to 2 μm account for a large proportion, but the ends of the graphene tubes are mostly closed morphology.

[0166] Example 9

[0167] (1) Weigh 0.95 g of urea (purity: 99%) and 0.05 g of calcium bicarbonate (particle size: 50 nm), place them in a quartz mortar and grind them for 30 min to obtain a mixed raw material;

[0168] (2) The mixed raw materials were placed in a graphite reaction chamber, and two layers of carbon cloth were placed 10 cm above the mixed raw materials;

[0169] (3) placing the graphite reaction chamber in a crucible, and then placing the crucible in a vacuum tube furnace;

[0170] (4) In a protective atmosphere, start the heating program of the vacuum tube furnace, starting from room temperature and heating to 1300°C at a heating rate of 10°C / min;

[0171] (5) The mixture was kept at 1300° C. for 30 min, and then the vacuum tube furnace was naturally cooled to room temperature. Black flocculent products were collected on the carbon cloth. The black flocculent products were micron-sized graphene tubes.

[0172] In the micron-sized graphene tubes obtained in Example 9, the bamboo-node morphology is obvious, but the proportion of graphene tubes with a tube diameter range of 1 to 2 μm is slightly smaller, and the graphene tubes are doped with oxygen elements.

[0173] Example 10

[0174] (1) Weigh 0.95 g of thiourea (purity: 99%) and 0.05 g of calcium sulfate (particle size: 50 nm), place them in a quartz mortar and grind them for 30 min to obtain a mixed raw material;

[0175] (2) The mixed raw material is placed in a graphite reaction chamber, and two layers of carbon cloth are placed 5 cm above the mixed raw material;

[0176] (3) placing the graphite reaction chamber in a crucible, and then placing the crucible in a vacuum tube furnace;

[0177] (4) In a protective atmosphere, start the heating program of the vacuum tube furnace, starting from room temperature and heating to 1500°C at a heating rate of 15°C / min;

[0178] (5) The mixture was kept at 1500° C. for 30 min, and then the vacuum tube furnace was naturally cooled to room temperature. Black flocculent products were collected on the carbon cloth. The black flocculent products were micron-sized graphene tubes.

[0179] In the micron-scale graphene tubes obtained in Example 10, the bamboo-node morphology is obvious, but the proportion of graphene tubes with a tube diameter range of 1 to 2 μm is small, and the graphene tubes are doped with sulfur.

[0180] Comparative Example 1

[0181] No calcium carbonate was added, only melamine was used as a blank control, and other conditions were kept consistent with those in Example 1. The collected graphene tubes were examined by scanning electron microscopy. Fig.25 The SEM image of the graphene tube of Comparative Example 1 with a scale of 50.0 μm is shown. Fig.26 The SEM image of the graphene tube of Comparative Example 1 with a scale of 10.0 μm is shown. Fig. 27 The SEM image of the graphene tube of Comparative Example 1 with a scale of 5.0 μm is shown. Fig.28 The SEM image of the graphene tube of Comparative Example 1 with a scale of 2.0 μm is shown. The graphene tube product of Comparative Example 1 is mainly a nanoscale tubular structure. Due to the lack of the effect of CaCO3, the tube has poor straightness and obvious curling, and the hollow structure and bamboo-node morphology are not obvious.

[0182] By comparing Example 1 and Comparative Example 1, it can be seen that the product obtained by carbonizing melamine as a blank experiment in the present invention is mainly a nanoscale tubular structure with obvious tube curling, low straightness, a tube diameter distribution of 100-200nm, a smooth tube wall, and almost no bamboo morphology. Only under the condition of a proppant, the prepared tubular structure has a size of micron level, obvious bamboo morphology, an open end of the tube, and an ultra-thick tube arm, and does not require a template as a support, and there is no tube collapse.

[0183] Comparative Example 2

[0184] The only difference from Example 1 is that the graphene tube cannot be successfully prepared when heated to 800°C.

[0185] Comparative Example 3

[0186] The only difference from Example 1 is that calcium carbonate is replaced with an equal amount of sodium carbonate, and graphene tubes cannot be successfully prepared.

[0187] Comparative Example 4

[0188] The only difference from Example 1 is that the calcium carbonate is replaced with an equal amount of sodium hydroxide, and graphene tubes cannot be successfully prepared.

[0189] In actual production, ultra-large-sized graphene tubes can be prepared by template-free batch rapid self-assembly according to the method of the embodiment of the present invention. An industrial-grade carbon source and auxiliary materials are selected and increased in equal proportions, and a simple powder mixture is performed. The powders are then loaded into a graphite reaction chamber for high-temperature carbonization treatment, and ultra-large-sized, high-purity, high-yield, bamboo-shaped micron-sized graphene tubes can be obtained.

[0190] The above is a detailed introduction to a method for preparing ultra-large-sized graphene tubes by rapid batch self-assembly without templates provided in an embodiment of the present invention. Specific examples are used herein to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core idea. At the same time, for those skilled in the art, according to the idea of ​​the present invention, there will be changes in the specific implementation methods and application scopes. In summary, the content of this specification should not be understood as limiting the present invention.

Claims

1. A method for preparing ultra-large-sized graphene tubes by rapid self-assembly in batches without templates, characterized in that: The following steps are involved: A carbon-containing substance that can self-assemble into a graphite-phase carbon nitride polymer is used as a carbon source, and an alkaline earth metal element and / or an alkaline earth metal compound is used as an auxiliary material, wherein the auxiliary material is one or more of calcium, magnesium, strontium, barium elements and their compounds, and the compound in the auxiliary material is an oxide, a halide, a carbonate, a bicarbonate or an alkali; the carbon source and the auxiliary material are uniformly mixed to obtain a mixed raw material; the auxiliary material accounts for 0.5 to 20% of the mass of the mixed raw material; The mixed raw material is placed in a graphite reaction chamber, and at least two layers of carbon cloth are arranged 1 to 10 cm above the mixed raw material; Placing the graphite reaction chamber in a crucible, and then placing the crucible in a vacuum tube furnace; In an oxygen-free environment, heating the mixed raw material to 900-3000° C. at a heating rate of 5-20° C. / min, and keeping the temperature for at least 30 minutes; After the vacuum tube furnace is cooled, black flocculent products are collected on the at least two layers of carbon cloth, and the black flocculent products are micron-sized graphene tubes; the proportion of graphene tubes with a tube diameter range of 1 to 2 μm in the micron-sized graphene tubes is ≥75%, and the length of the micron-sized graphene tubes is ≥50 μm.

2. The method for preparing super-large-sized graphene tubes by rapid self-assembly without template in batches according to claim 1, characterized in that: The carbon source is one or more of cyanamide, dicyandiamide, melamine, urea, thiourea, cyanuric acid and cyanuric chloride.

3. The method for preparing super-large-sized graphene tubes by rapid self-assembly without template in batches according to claim 1, characterized in that: The calcium compound in the auxiliary material is one or more of calcium carbonate, calcium bicarbonate, calcium oxide, calcium hydroxide, calcium chloride and calcium fluoride.

4. The method for preparing super-large-sized graphene tubes by rapid self-assembly without template in batches according to claim 1, characterized in that: The oxygen-free environment is a vacuum environment, or the oxygen-free environment is created by a protective atmosphere.

5. The method for preparing super-large-sized graphene tubes by template-free batch rapid self-assembly as claimed in claim 1, characterized in that: The process of obtaining the mixed raw material comprises: S11, grinding the carbon source and the auxiliary material in a mortar to obtain a first mixed material; S12, dispersing the first mixed material in deionized water to obtain a homogeneous suspension; S13, heating and drying the homogeneous suspension in a water bath to obtain a second mixed material; S14, grinding the second mixed material in a mortar to obtain the mixed raw material.

6. The method for preparing super-large-sized graphene tubes by rapid self-assembly without template in batches according to claim 5, characterized in that: In step S12, the mass of the deionized water is 5 to 10 times that of the first mixed material; In step S13, the temperature range of the water bath condition is 50-70°C.

Citation Information

Patent Citations

  • Method for preparing high-ratio graphite-type nitrogen-doped graphene tube in template-free one-step method

    CN105731443A

  • Method for large-scale catalytic preparation of graphene tubes by template-free method

    CN116443864A